High SARS-CoV-2 infection rates and viral loads in community-dwelling individuals from rural indigenous and mestizo communities from the Andes during the first wave of the COVID-19 pandemic in Ecuador - Morales-Jadán, Diana; Vallejo-Janeta, Alexander Paolo; Bastidas, Vanessa; Paredes-Espinosa, Maria Belen; Freire-Paspuel, Byron; Rivera-Olivero, Ismar; Ortiz-Prado, Esteban; Henriquez-Trujillo, Aquiles Rodrigo; Lozada, Tannya; , The UDLA COVID-19 Team; Garcia-Bereguiain, Miguel Angel; Jaramillo, Tatiana; et al. (Frontiers in Medicine, 2023)
Background Neglected indigenous groups and underserved rural populations in Latin America are highly vulnerable to COVID-19 due to poor health infrastructure and limited access to SARS-CoV-2 diagnosis. The Andean region in Ecuador includes a large number of isolated rural mestizo and indigenous communities living under poverty conditions. Objective We herein present a retrospective analysis of the surveillance SARS-CoV-2 testing in community-dwelling populations from four provinces in the Ecuadorian Andes, carried out during the first weeks after the national lockdown was lifted in June 2020. Results A total number of 1,021 people were tested for SARS-CoV-2 by RT-qPCR, resulting in an overall high infection rate of 26.2% (268/1,021, 95% CI: 23.6–29%), which was over 50% in several communities. Interestingly, community-dwelling super spreaders with viral loads over 108 copies/mL represented 7.46% (20/268, 95% CI: 4.8–11.1%) of the SARS-CoV-2 infected population. Conclusion These results support that COVID-19 community transmission in rural communities from the Andean region was happening at the early stages of the COVID-19 pandemic in Ecuador and point out the weakness of the COVID-19 control program. Community-dwelling individuals in neglected rural and indigenous communities should be considered for a successful control and surveillance program in future pandemics in low- and middle-income countries.